Sustainable CO2 capture via adsorption by chitosan-based functional biomaterial : A review on recent advances, challenges, and future directions - Foong, S. Y.; Chan, Y. H.; Yiin, Chung Loong; Lock, Serene Sow Mun; Loy, Adrian Chun Minh; Lim, J. Y.; Yek, P. N. Y.; Wan Mahari, W. A.; Liew, R. K.; Peng, W.; Tabatabaei, M.; Aghbashlo, M.; et al. (Elsevier, 2023)
Chitin is a naturally occurring biopolymer, while chitosan is a deacetylated derivative of chitin. The unique properties of chitin/chitosan, such as nitrogen-rich, biodegradability, non-toxicity, high adsorption capacity, and biocompatibility, allow them to be utilized as precursors for CO2 adsorbents in pursuing the circular economy. This review provides a detailed overview of chitosan-based biomaterials as adsorbents for CO2 capture, focusing on extraction techniques, specialized treatments, adsorbent synthesis methodologies, and the CO2 capture performance of the resultant adsorbents. In general, current extraction techniques are still dominated by chemical and biological means, but more efficient and environmental-friendly techniques are emerging and developing towards maturity. The structural characteristics of modified/functionalized chitosan-based adsorbents and the effect of adsorption process parameters on CO2 uptake are reviewed to highlight their potential in CO2 capture. Besides the conventional treatments of carbonization and chemical activation, incorporating oxide nanoparticles, clay, metal-organic framework, and zeolites to form hybrid chitosan-based CO2 adsorbents showed promising performance in CO2 capture. The morphology, structural, and surface chemistry characteristics were reported to show enhancement after treatments. Based on literature screening, the highest CO2 adsorption capacity reported was ∼8 mmol/g adsorbent with 1 nm micropores and 2 nm mesopores favorable for CO2 adsorption at atmospheric pressure and elevated pressure, respectively. Furthermore, the technological gaps and limitations of each extraction and synthesis technique, overall challenges, and outlook are elucidated. The hybridization of adsorbent synthesis and modification methods could be the main way to enhance the adsorbent performance, economic viability, and environmental sustainability in the commercial-scale context.